2010
DOI: 10.1016/j.atherosclerosis.2010.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase inhibitors attenuate atherogenesis in apolipoprotein E-knockout mice

Abstract: The present study revealed novel anti-oxidative and anti-atherosclerotic effects of pharmacological stimulation of cholinergic system by donepezil. Donepezil may be used as a novel therapeutics for the atherosclerotic cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…In this study, the dose of donepezil administrated to rats was 5.0 mg/kg/day, which was about 50 times higher than the therapeutic doses used in the clinical setting. However, although different from that used in humans, a daily dose of 5.0 mg/kg has been extensively used in animal studies without any side effects [13,23]. In a preliminary study, we confirmed that this dose of donepezil was the submaximal dose that did not cause side effects such as vomiting, diarrhea, anorexia, or growth retardation.…”
Section: Discussionsupporting
confidence: 70%
“…In this study, the dose of donepezil administrated to rats was 5.0 mg/kg/day, which was about 50 times higher than the therapeutic doses used in the clinical setting. However, although different from that used in humans, a daily dose of 5.0 mg/kg has been extensively used in animal studies without any side effects [13,23]. In a preliminary study, we confirmed that this dose of donepezil was the submaximal dose that did not cause side effects such as vomiting, diarrhea, anorexia, or growth retardation.…”
Section: Discussionsupporting
confidence: 70%
“…In ATH, perhaps surprisingly, donepezil infusion could attenuate atherogenesis in susceptible mice [279]. …”
Section: Discussionmentioning
confidence: 99%
“…Donepezil, another centrally acting and FDA-approved acetylcholinesterase inhibitor, suppresses CCL2 and TNF expression, attenuates athero-sclerosis and improves long-term survival following chronic heart failure in rodents. 120,121 These findings suggest that centrally acting acetylcholinesterase inhibitors could potentially be developed for the treatment of atherosclerosis.…”
Section: Therapeutic Implicationsmentioning
confidence: 93%